2019
DOI: 10.1007/s42729-019-00059-2
|View full text |Cite
|
Sign up to set email alerts
|

P Pools After Seven-Year P Fertiliser Application Are Influenced by Wheat Straw Addition and Wheat Growth

Abstract: Little is known about the effect of long-term P fertilisation on soil P pools and how they are influenced by straw addition and plant growth. Two experiments were carried out with soil which had been amended with 0, 10 and 20 kg P ha −1 for 7 years (referred to 0P, 10P, 20P). In experiment 1, soil was incubated moist for 4 months without or with 5 g kg −1 barley straw (C/P 255). Then wheat was grown for 4 weeks. In experiment 2, wheat was grown for 5, 10 and 15 weeks. HCl P, citrate P, resin P and microbial bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In addition, Yang et al (2020) reported that complete decomposition of straw leads to the enhancement release of straw C and N into the soil which improved soil nutritional condition. However, Hoang and Marschner (2019) found that straw addition could decrease available N, compared with without straw addition. In present study, straw incorporation coupled with deep placement of N fertilizer treatment substantially improved the NRE and NAE.…”
Section: Nitrogen Use Efficiencymentioning
confidence: 92%
“…In addition, Yang et al (2020) reported that complete decomposition of straw leads to the enhancement release of straw C and N into the soil which improved soil nutritional condition. However, Hoang and Marschner (2019) found that straw addition could decrease available N, compared with without straw addition. In present study, straw incorporation coupled with deep placement of N fertilizer treatment substantially improved the NRE and NAE.…”
Section: Nitrogen Use Efficiencymentioning
confidence: 92%
“…Crop straw is one of the important organic fertilizers, which can increase available C and N in the soil and improve soil physicochemical properties (Wang et al 2015;Hoang and Marschner 2019). But straw returning observably affects CH 4 emissions from rice fields (Ma et al 2009;Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, phosphorus and potassium are often the main elements that limit crop growth and yield. Although chemical fertilizers can provide phosphorus and potassium for plant, the utilization efficiency is low (Hoang and Marschner 2019). Moreover, chemical fertilizers with long-term use will cause groundwater and environmental pollution.…”
Section: Discussionmentioning
confidence: 99%